EFEK PEMBERIAN INFUSA KOMBINASI TEMU IRENG, TEMULAWAK, KENCUR DAN JAHE TERHADAP BERAT MENCIT GALUR SWISS-WEBSTER - Indira Pipit Miranti; Arinda Nur Cahyani; Eko Hidayaturohman; Ninstar Fathina Rifa (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2025)
Signs that children have difficulty eating and will then trigger malnutrition are very limited nutritional intake and a reduced appetite. Temu ireng, curcuma, sand ginger and ginger rhizomes contain essential oils, curcumin, xanthorizol, gingerol and flavonoids in each plant which can increase body weight and appetite. The purpose of this study was to determine the effect and optimal frequency of infusion combination on body weight and feed consumption of mice. The research was conducted in the Pharmacology Laboratory of STIKes Ibnu Sina Ajibarang. This type of research is true experimental with pre-post-test control design method. 28 male mice were divided into four groups. Group P0 (aquadest), group P1 (½ x dose), group P2 (1x dose) and group P3 (1 ½ x dose). All treatment groups were acclimatized for 7 days, then treated according to the predetermined dose, then observed body weight gain and feed consumption for 28 days. Data analysis was conducted using paired t-test, One Way ANOVA test, and Post-hoc LSD test. The results showed that there was a significant effect on body weight gain in group P2 (p=0.000) and feed consumption in all groups in the first, third and fourth weeks. (p<0,05).   Keywords; Effect, Body Weight, Infusa, Rhizome.